"We have those kinds of conversations here …": Addressing contentious politics with elementary students. (March 2019) - Payne, Katherina A.; Journell, Wayne
Abstract: A particularly contentious event, the 2016 U.S. Presidential Election presented distinct challenges to identity politics in the classroom. This article examines a case study of a White fifth-grade elementary teacher, working with primarily youth of color, who did not shy away from teaching this contentious topic. This case illustrates the possibilities for teaching contentious political issues by drawing on the relational aspects of teaching and students' politicized funds of knowledge. Additionally, we examine the teaching of contentious political issues in an elementary setting with students who often are positioned as "too young" to engage with issues that affect their daily lives. Highlights: Case study of an exceptional elementary teacher who engaged with contentious political issues. UsesSondel et al.'s (2018) pedagogy of political trauma. An example of how contentious identity politics can be broached with young learners. Explores teaching in the aftermath of the 2016 U.S. Presidential Election.